Red Beet Biotechnology 2012
DOI: 10.1007/978-1-4614-3458-0_16
|View full text |Cite
|
Sign up to set email alerts
|

Techno-commercial Aspects of Relevance to Red Beet

Abstract: While Chap. 1 of this book provides an overview of what has been researched in red beet, this chapter tries to put red beet into the newer arena of diverting its current progress towards newer technologies and applications. Beets have unlimited applications, from food, fodder, fuel and pharmaceutical to ornamentals and environmental cleansing agents; this means that the allied technologies span from moderate to very high-tech ventures. Scienti fi cally, as a model system, beet has contributed continuously to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Betalain pigments, uniquely produced in the plant order Caryophyllales (e.g. beets, cactus), have antioxidant activities and reported anticancer and antidiabetic properties (Kanner et al ., ; Lee et al ., , ; Tesoriere et al ., ), and are the major natural red dye (E162) used in the US food industry (Gaertner and Goldman, ; Neelwarne, ). Thus, enhancing the production of tyrosine and its derivatives can improve nutritional and pharmaceutical values of plants.…”
Section: Introductionmentioning
confidence: 99%
“…Betalain pigments, uniquely produced in the plant order Caryophyllales (e.g. beets, cactus), have antioxidant activities and reported anticancer and antidiabetic properties (Kanner et al ., ; Lee et al ., , ; Tesoriere et al ., ), and are the major natural red dye (E162) used in the US food industry (Gaertner and Goldman, ; Neelwarne, ). Thus, enhancing the production of tyrosine and its derivatives can improve nutritional and pharmaceutical values of plants.…”
Section: Introductionmentioning
confidence: 99%
“…27 These pigments are currently used as major sources of natural red dyes in the food industry in the United States, where heat stability is not a primary limitation. 28 The use of natural food colorants is becoming popular in recent years due to concerns over the safety of synthetic dyes. 29 In addition, betalain-based food dyes do not stain and thus are sought after for processed foods, as well as frozen and refrigerated dairy products.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recent studies showed that betalains have antioxidant activities and a number of beneficial health-related properties, such as induction of phase II enzymes that offers protection against certain cancers, inhibition of the expression of Intercellular Adhesion Molecule-1 , a response factor in the inflammatory reaction, to protect endothelium, and cytotoxic effects on various types of cancer cells . These pigments are currently used as major sources of natural red dyes in the food industry in the United States, where heat stability is not a primary limitation . The use of natural food colorants is becoming popular in recent years due to concerns over the safety of synthetic dyes .…”
Section: Introductionmentioning
confidence: 99%